Assessing the errors in shortwave radiative fluxes inferred from the Geostationary Earth Radiation Budget (GERB) instrument in the presence of dust aerosol - Brindley,HE; Russell,JE (GASTRIC CANCER, 2008)
The Geostationary Earth Radiation Budget (GERB) instruments flying on the Meteosat Second Generation series of satellites provide a unique tool with which to monitor the diurnal evolution of top-of-atmosphere broadband radiation fields. GERB products, which have recently been released to the scientific community, include aerosol information in addition to the observed radiances and inferred fluxes. However, no account of the anisotropic characteristics of aerosol has been incorporated in the radiance-to-flux conversion, which uses angular distribution models developed for clear or cloudy conditions. Here an attempt is made to quantify the impact of this omission in the shortwave (SW), focusing on dust-contaminated scenes. An observationally based representation of dust is used to develop a theoretical angular distribution model, which is tested through comparison with observed GERB radiances. For dusty scenes that have been processed as clear ocean, applying the dust model to convert GERB radiances to fluxes reduces the SW reflected flux by an average of approximately 12 W m(-2) relative to the original GERB fluxes. This value ranges from -4 to +55 W m(-2), depending on observation geometry and dust loading. For dusty scenes that the GERB processing has treated as cloudy, GERB fluxes are generally smaller than values obtained using the dust-specific model. On average, over the time period studied here, the two effects partially cancel, and the overall mean difference is 2.5 W m(-2). However, it is shown that this cancellation is highly sensitive to the location and time period under consideration.